2013
DOI: 10.1111/ddi.12112
|View full text |Cite
|
Sign up to set email alerts
|

A highly aggregated geographical distribution of forest pest invasions in theUSA

Abstract: Aim Geographical variation in numbers of established non-native species provides clues to the underlying processes driving biological invasions. Specifically, this variation reflects landscape characteristics that drive non-native species arrival, establishment and spread. Here, we investigate spatial variation in damaging non-native forest insect and pathogen species to draw inferences about the dominant processes influencing their arrival, establishment and spread.Location The continental USA, including Alas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
120
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 45 publications
5
120
0
Order By: Relevance
“…For example, the 2002 U.S. federal budget for NIS control and related activities was reported at $777 million, and expenditures have increased to [$2.2 billion by 2016 (https://www.doi.gov/invasivespecies/nisc-resources, accessed 16 January 2017). Threats, or at least anticipation of impending impacts, continue to increase with arrival of new NIS (Mills et al 1994(Mills et al , 2003van Wilgen et al 2012;Liebhold et al 2013;Langor et al 2014). NIS may negatively impact native species, communities, ecosystem processes such as fire regimes, nutrient cycling, decomposition, pollination, hydrology, food webs, and the ability to manage habitats for declining native species (Mack et al 2000;Zuefle et al 2008;Burghardt et al 2009;Kessler et al 2011;Powell et al 2011Powell et al , 2013Simberloff 2011;Gaertner et al 2014;Downey and Richardson 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the 2002 U.S. federal budget for NIS control and related activities was reported at $777 million, and expenditures have increased to [$2.2 billion by 2016 (https://www.doi.gov/invasivespecies/nisc-resources, accessed 16 January 2017). Threats, or at least anticipation of impending impacts, continue to increase with arrival of new NIS (Mills et al 1994(Mills et al , 2003van Wilgen et al 2012;Liebhold et al 2013;Langor et al 2014). NIS may negatively impact native species, communities, ecosystem processes such as fire regimes, nutrient cycling, decomposition, pollination, hydrology, food webs, and the ability to manage habitats for declining native species (Mack et al 2000;Zuefle et al 2008;Burghardt et al 2009;Kessler et al 2011;Powell et al 2011Powell et al , 2013Simberloff 2011;Gaertner et al 2014;Downey and Richardson 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies in Europe have shown negative relationships between tree species richness and the abundance of invasive tree-feeding insects at the plot or stand scale (Jactel et al 2006;Guyot et al 2015). Conversely, in the USA, a positive relationship between native tree species richness and the number of successful invasions by non-native tree-feeding insects was observed (Liebhold et al 2013), although that study assessed larger-scale county-level data that are not directly comparable with plot-level data.…”
Section: Effects Of Forest Tree Diversity On Pest Regulation Of Nativmentioning
confidence: 93%
“…Conversely, because most tree-feeding insects are relatively host-specific, an unavoidable consequence of greater tree diversity is that it leads to an increase in the number of host trees that may be colonised by potential invaders (Liebhold et al 2013). Ultimately, the extent of realised invasions depends on the combined net effect of negative and positive effects of tree species richness.…”
Section: Effects Of Forest Tree Diversity On Pest Regulation Of Nativmentioning
confidence: 99%
“…Outbreaks decimate forests and, in some instances, result in the local elimination of tree species [5,6] substantially changing forest ecosystems [1,7]. Among North American forests, the northeastern region is being particularly affected by these introductions [8,9], and one of the most recent pests arriving to this area is the emerald ash borer, Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) [10].…”
Section: Introductionmentioning
confidence: 99%